PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN (Studi pada Pelanggan Members Game Center Skyland Kota Semarang) - Yudha Nugroho, Ariadi; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2018)
Game center is one of the business opportunities in the service sector with a growing potential market, so that business people take advantage of the opportunity to create a game center. This research was conducted to analyze the effect of Product Quality, Service Quality, and Price Perceptions on Customer Loyalty with a survey on Members Of Skyland Game Center. Data collection technique conducted in this study is a questionnaire. The sample was chosen by non probability sampling technique. Respondents in this research are Members of Skyland game center with a total of 95 respondents with the criteria of at least 3 times using the service. The technique used to analyze the influence of independent variables and dependent variable of this research is linear regression analysis. Result of research prove that hypothesis one Product Quality have positive effect to Customer Loyalty accepted. The second hypothesis of Service of Quality has a positive effect on Customer Loyalty accepted. The third hypothesis of price persepsion has a negative effect on Customer Loyalty was reject. Coefficient of determination test results stated that the three independent variables have an influence of 44.9% of Customer Loyalty. Skyland Game Center is expected to make the price more relevant and more affordable by knowing consumer preferences that can make consumer loyalty increase.